The efficacy of bipolar and multipolar radiofrequency ablation of lung neoplasms - results of an ablate and resect study - Schneider, Thomas; Reuss, David; Warth, Arne; Schnabel, Philipp A.; von Deimling, Andreas; Herth, Felix J.F.; Dienemann, Hendrik; Hoffmann, Hans (European journal of cardio-thoracic surgery, 2011)
Abstract Objective: Radiofrequency ablation (RFA) has obtained increasing attention as an interventional approach for the local treatment of primary and secondary lung neoplasms. The local effect of the procedure is usually controlled by radiologic means. The objectives of this 'ablate and resect' study were to investigate the efficacy of bipolar and multipolar RFA by histologic evaluation and to compare the two techniques. Methods: In a total of 32 subjects with histologically proven non-small-cell lung cancer or pulmonary metastases from an extrathoracic primary tumor, bipolar, or multipolar RFA was performed during open thoracotomy. Curative resection (lobectomy or wedge resection including mediastinal lymph node dissection) was performed subsequently. The extent of cell death and early histologic findings following RFA were determined by histology and immunohistochemistry (nicotinamide adenine dinucleotide (NADH) and monoclonal anti-mitochondrial antibodies MAB 1273). Results: Intra-operative bipolar and multipolar RFA is a safe procedure, and there was no bleeding or thermal damage of the lung tissue. Routine histologic staining could not identify tumor cell death. However, immunohistochemistry was able to verify cell death in the ablated tumor tissue. Complete tumor cell necrosis was determined in 12 tumors (37.5%); and scattered vital tumor tissue was detected in 16 tumors (50%). Incomplete ablation with a ratio of >20% vital tumor tissue was found in four tumors (12.5%), particularly surrounding vascular structures within the tumor tissue or in marginal zones of the tumor tissue. The local efficacy of bipolar and multipolar RFA was comparable, and incomplete ablations were found only in adenocarcinoma. Conclusions: Bipolar and multipolar RFA in an open thoracotomy setting is a technically feasible and safe procedure. Early immunohistochemical findings after RFA showed complete tumor cell necrosis in 38% of cases. The high rate of viable tumor cells remaining after ablation casts doubt on RFA as a curative concept. This approach should be reserved for palliative indications. Patients fulfilling the criteria for curative resection should not be denied surgery.